Answer:
12=12
Step-by-step explanation:
2a = b
a -3b =12
To solve, set one of the equations equal to zero. The first equation is actually already set to 0.
b = 2a
Now you can plug this equation into the other one, by substituting the b in the equation with this.
a -3b = 12
a – 3(2a) = 12
Now all you have to do is distribute the 3 (multiply the number outside the parenthesis, 3 in this case, by everything inside).
a – 6a = 12
Combine like terms. Since we have 1 positive a and 6 negative ones, we subtract the two numbers without the signs
6-1 = 5
And take the sign of the larger number. Since 6 is large and 6 is negative, we are left with
-5a = 12
Now solve for a, which in this case means dividing both sides by -5
a = -12/5
Simplify
a = -2.4
Now that you have a, it’s easy to find b
b = 2a
b = 2(-2.4)
b= -4.8
Now you check your work by plugging your new a and b into either equation to see if it’s true.
-4.8 = 2(-2.4)
-4.8 = -4.8
And just for laughs let’s try the other equation
a -3b =12
-2.4 – 3(-4.8) = 12
Distribute the 3 again. Remember that when two negative numbers are multiplied they become positive.
-2.4 +14.4 = 12
12 = 12
Create a system of equations
x + y = 123
5x + y = 343
I use substitution
y = 123 - x
5x + 123 - x = 343
4x + 123 = 343
4x = 220
x = 55
Plug in
x + y = 123
55 + y = 123
y = 68
Check
5x + y = 343
5(55) + 68 = 343
275 + 68 = 343
343 = 343
Answer:
59
Step-by-step explanation:
100/1.7=58.8
Answer:
40
Step-by-step explanation:
(2/5)*n - 6 = 10 Add 6 to both sides
(2/5)*n - 6 + 6 = 10 + 6 Combine
(2/5)*n = 16 Multiply both sides by 5/2
(5/2)(2/5)n = 16*(5/2)
n = 80 / 2
n = 40